Analysis of the Opinion of Ustadz Abdul Somad on the Concept of the Sakinah Family - Pastabikul Randa (Proceedings of The ICECRS, 2021)
Islam regulates everything in human life, one of which is the problem of marriage. And today many of the Muslims will fail in fostering a sakinah family, and finally they separate. Whereas Islam does not like it all, because Islam teaches every Muslim how to choose a partner, so it does not cause damage in the household for those who follow the instructions in Islam. And therefore Muslims need sakinah family concepts to practice in their families everyday, so as not to confuse them in practicing them and make it easier for them to practice them. The type of research used is quantitative. The method of collecting data is obtained through review of books and video. While the analysis used is the opinion of Ustadz Abdul Somad About the Sakinah Family. Based on the results of the discussion in this paper that building a sakinah family must begin before marriage and after marriage. As for before marriage, he prepared religion and entered Islamic communities to indulge in immorality. As for after marriage, he maintains the feelings of his partner, so that growing love and affection between the two.